Optimization Cost of Transportation by Applying Linear Programming - MAHADI, MOHAMMED KHAIRUL AZHARI; KAMARDAN, MUHAMAD GHAZALI (Enhanced Knowledge in Sciences and Technology, 2022)
The term "optimization" refers to the most effective use of resources and available technologies. Many difficulties are solved as a result of better planning and execution. Better results can be achieved using quantitative models and mathematical methods such as linear programming. For this research, we want to determine the minimum cost of transportation problem for the product A to be delivered from three different companies warehouses to seven different distributor’s warehouses. Mathematical methods are used to solve transportation issues. The majority of these problem are modelled using the linear programming method. In this paper, application of a transportation problem that involves transporting product A from company’s warehouse to distributor’s warehouse is modeled using linear programming in order to find the optimum transportation cost. Excel Solver has been used to model and solve this problem. The result of this research will give benefit for the company.